Punitive justice in the Malaysian criminal law and its sustainability: balancing the rights of offenders with those of the victims - Hussin, Nasimah (2011)
Punitive justice as exercised in Malaysia today is retributive and rehabilitative in nature. It is a theory of justice that considers punishment as an acceptable response to crime. Many parts of this world use the same theory in their legal documentation. The concept reflects “an eye for an eye” and let the punishment fit the crime. Any criminal act that is committed by the accused is considered as a breach of state’s right and it is not a wrong against the victim. Some argue that the role of criminal justice system should reflect both the offender and the victim involved. The current system’s channel of communication is criminal-centric and it serves as the medium to punish and rehabilitate the offender. It neglects its role to create self consciousness on responsibility and accountability towards the damage that has been done. In addition, as too much emphasis is given with respect to the rights of offenders, the authority tends to ‘invest’ more on them, without any thought of reaping any benefit from the amount expended. Thus, this paper will discuss this scenario in the Malaysian context. It will examine the existing legal framework in Malaysia to check the extent of which it secures the rights of offender and those of the victim and to suggest reforms to the system so that it is responsive and receptive to both parties.